Edith Penrose's Contributions to the Resource‐based View: An Alternative Perspective - Lockett, Andy; Thompson, Steve (Journal of Management Studies, 2004)
ABSTRACT Edith Penrose's work has been widely acknowledged to have played a central role in providing the intellectual foundations of the resource‐based view. This position, however, was recently challenged in a paper by Rugman and Verbeke (2002). In this paper we address the three main arguments of Rugman and Verbeke and, by drawing on her writings, demonstrate that their arguments are materially incorrect. While readily conceding that Penrose's primary goal was to explain the growth of firms, we show that her analysis of path‐dependent firm evolution anticipated many key propositions of the resource‐based view.